The extent to which balance score card is used in aviation sector (An Empirical Study on Royal Jordanian Airlines) - Mohammad, Ahmad Saleh Alnaimat (НУБіП України, 2018)
The objective of this study was to assess the practicalities of the application of the Balanced Scorecard at Royal Jordanian Airlines, which was the sole subject of the study. The financial statements published for the years (2014–2015) were analyzed and personal interviews with relevant company employees were conducted in order to assess the financial performance using the Balanced Scorecard. The results of the study concluded the presence of the effect of the application and use of the four axes of the Balanced Scorecard on performance measures based on indications of accounting profit (rate of return on assets and rate of return on equity) at Royal Jordanian Airlines. As well as having the effect of the application and use of Balanced Scorecard four axes on modern performance measures Accounting Profit (measure of economic value added, market value added) at Royal Jordanian Airlines. In the light of these results, the researcher recommends that RJA makes the necessary efforts to build robust foundations for the assessment of its strategic performance based on the application and use of various aspects of the Balanced Performance Card in such a way as to emphasize the conformity of predefined objectives with the strategy the company decided to adopt to cope with the rapid changes and developments characteristic of an intensely competitive business environment.
Ступінь коригування балансової системи в авіаційному секторі (емпіричне дослідження - Royal Jordanian Airlines)
Метою даного дослідження було оцінити практичні аспекти застосування збалансованої системи показників у Royal Jordanian Airlines, що було єдиним предметом дослідження. Проаналізовано фінансову звітність, опубліковану на протязі багатьох років (2014-2015 рр.), і проведені персональні інтерв'ю з відповідними працівниками компанії для оцінки фінансових результатів за допомогою збалансованої системи показників. Результати дослідження підтвердили наявність впливу застосування та використання чотирьох осей збалансованої системи показників на показники ефективності, що базуються на показниках облікового прибутку (норми доходності активів та норми прибутку на власний капітал) у Royal Jordanian Airlines. Окрім впливу застосування і використання Balanced Scorecard чотирьох осей на сучасні показники діяльності обліку прибуток (міра економічної доданої вартості, доданої 57 ринкової вартості) у Royal Jordanian Airlines. З огляду на ці результати, дослідник рекомендує, щоб RJA зробив необхідні зусилля для створення надійних підвалин для оцінки його стратегічних результатів на основі застосування та використання різних аспектів роботи з картою збалансованих результатів роботи таким чином, щоб підкреслити відповідність від заздалегідь визначених завдань із стратегією, яку компанія вирішила прийняти, щоб впоратись із швидкими змінами та подіями, характерними для сильно конкурентного ділового середовища.
Keywords: balanced scorecard; Royal Jordanian Airlines; збалансована система показників